Mediating Role of Community Participation on the Relationship between Common Passion and Sustainable development (Journal of Governance and Development (JGD), 2016)
The purpose of this study is to explore the influence of common passion on community participation. It further demonstrates the relationship between common passion, community participation and sustainable development. A combination of quantitative and qualitative methods was employed. A sample of 284 respondents from six communities were used while 24 interviewees were interviewed amongst 24 key community leaders in three selected oil producing states in the Niger Delta region, Nigeria. The research findings indicate that community participation plays crucial role in community development sustainability. Further results from both analysis shows the common passion has a positive influence on community participation and sustainable development. More so, community participation was found as a mediator on the relationship between common passion and sustainable community development. This study is limited in scope, coverage and of course generalisation. It is limited to the Niger Delta region of Nigeria which is believed to be the richest among other regions in Nigeria. Thus, other regions in Nigeria were not put into consideration. The present study has created awareness and knowledge about the current state of development in the Niger Delta region of Nigeria. Secondly, it offers a framework to guide policy formulation, implementation and evaluation for sustainable development in the Niger delta region of Nigeria. It has also increased an understanding on the key factors that influence sustainable development of the Niger Delta people. The study offered an insightful result for the policy makers in government, non-governmental agencies and researchers in this field of study. The study contributes to community development practices and sustainability by identifying the relevance of group cohesion, interaction and common purpose as crucial element in facilitating community participation. The research opens up avenue for future study in examining those factors that stimulates community solidarity and group cohesion as catalyst for community driven development sustainability.